Examining IT Service Management Service Operations Utilizing The ITIL V3 Framework: A Case Study of Dana - Zulkarnain; Anthony; Elvin Valentino; Keaton Yoputra; Mulyanto; Nellsen Purwandi (Fakultas Teknik Universitas Lambung Mangkurat, 2024)
This paper presents a comprehensive analysis of IT service management (ITSM) service operations within the context of the ITIL v3 framework, focusing on a case study of Dana, a digital wallet company. Employing a quantitative research approach through a questionnaire, the study delves into Dana's implementation of ITIL v3 practices in managing its IT services. It investigates various aspects of IT service operations, encompassing event management, incident management, problem management, request fulfillment, and access management, within the framework of ITIL v3 and maturity model. By scrutinizing Dana's ITSM service operations, this study aims to offer insights into the effectiveness and challenges of applying the ITIL v3 framework in real-world organizational settings. The research findings contribute to the existing knowledge on IT service management practices and provide practical recommendations for organizations striving to optimize their IT service operations using ITIL v3 principles.